PEMETAAN NILAI LAHAN DI KECAMATAN AUR BIRUGO TIGO BALEH KOTA BUKITTINGGI - Fenni Febriati; yurni suasti; febriandi andi (DEPARTEMEN GEOGRAFI FIS UNP, 2017)
This study aims to: (1) to map the value of land in the district Aur Birugo Tigo Baleh Bukittinggi, (2) analyze the influence of developer activity on the value of land in the district Aur Birugo Tigo Baleh. This type of research is quantitative descriptive. The study population is an area of research is landuse of the District Aur Birugo Tigo Baleh Bukittinggi and sample in the context of secondary data that regions associated with parameter determining land values (accessibility of land positive and accessibility of land negative, public facility), the samples in the context of data primary ie population per village in the district Aur Birugo Tigo Baleh. This study found that: (1) the value of land in District Aur Birugo Tigo Baleh (ABTB) ranged between Rp. 500,000 / m2 up to Rp. 4,800,000 / m2 (2) Determinants of land values in the form of land use, land accessibility of positive, negative land accessibility, and public facilities do not always affect the height of the low value of the land. Land that has land use form fields and plantations are not always affect the value of the land is low, low positive land accessibility does not necessarily affect the value of the land to be low, as well as the accessibility of land which has a low negative land does not necessarily affect the value of the land to be high.